Bibliometric insights from publications on subchondral bone research in osteoarthritis - Wen, Pengfei; Liu, Rui; Wang, Jun; Wang, Yakang; Song, Wei; Zhang, Yumin (Frontiers in Physiology, 2022)
Background: The role of subchondral bone in the pathogenesis of osteoarthritis has received continuous attention worldwide. To date, no comprehensive bibliometric analysis of this topic has been carried out. The purpose of this study was to investigate the knowledge landscape, hot spots, and research trends in subchondral bone research through bibliometrics. Methods: Web of Science Core Collection database was used to collect articles and reviews on subchondral bone in osteoarthritis published between 2003 and 2022. CiteSpace, VOSviewer, Scimago Graphica, and a bibliometric online analysis platform (http://bibliometric.com/) were used to visualize the knowledge network of countries, institutions, authors, references, and keywords in this field. Both curve fitting and statistical plotting were performed using OriginPro, while correlation analysis was done using SPSS. Results: A total of 3,545 articles and reviews were included. The number of publications on subchondral bone showed an exponential growth trend. The USA produced the most (980), followed by China (862) and the United Kingdom (364). Scientific output and gross domestic product were significantly correlated (r =0.948, p＜0.001). The University of California System and Professor Pelletier Jean-Pierre were the most prolific institutions and influential authors, respectively. The most active and influential journal for subchondral bone research was Osteoarthritis and Cartilage. The majority of papers were financed by NSFC (474, 13.4%), followed by HHS (445, 12.6%), and NIH (438, 12.4%). In recent years, hot keywords have focused on the research of pathomechanisms (e.g. inflammation, apoptosis, pathogenesis, cartilage degeneration/repair, angiogenesis, TGF beta) and therapeutics (e.g. regeneration, stromal cell, mesenchymal stem cell). Conclusions: Subchondral bone research in osteoarthritis is flourishing. Current topics and next research trends would be centered on the pathomechanisms of cellular and molecular interactions in the subchondral bone microenvironment in the development of osteoarthritis and the exploration of targeted treatment medicines for the altered subchondral bone microenvironment.